Pengaruh Logistics Service Quality Terhadap Customer Satisfaction dan Customer Loyalty Pada Pengguna JNE dan J&T Express di Jabodetabek : The Effect of Logistics Service Quality on Customer Satisfaction and Customer Loyalty on JNE And J&T Express Users in Jabodetabek - Khairi, Lukluk Ilmatul; Cahyadi, Eko Ruddy (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The increase in the number of e-commerce users has led to the trend of online shopping becoming popular among Indonesians during the COVID-19 pandemic. Logistics provider services have an important role in the development of an e-commerce. JNE and J&T Express are logistics industry companies in Indonesia. This study aims to analyze the influence of logistics service quality on customer satisfaction and customer loyalty among JNE and J&T Express users in Jabodetabek. The data in this study were obtained through primary data and secondary data. The data analysis used was the Independent Sample T-Test and SEM-AMOS analysis with a sample of 407 respondents. The sampling technique is a non-probability sampling method with the type of convenience sampling. The results of the Different Test analysis show that 17 of the 27 indicators provide positive and significant t-count values. It can be concluded that the performance level of J&T Express is better and superior compared to JNE. The managerial implication in this study is that the quality aspect of order fulfillment is a top priority because it has the greatest influence among other aspects. The quality aspect of order fulfillment that is important to improve is the condition of the package when it is received safely and undamaged and the company's consistency in maintaining the package properly. The results of this study indicate that logistics service quality has a positive and significant effect on customer satisfaction and customer loyalty. Keywords: customer satisfaction, service quality, loyalty, SEM AMOS, logistics service